Optimalisasi Kesejahteraan Psikologis Individu LGBT Melalui Konseling Kelompok Berbasis Rational Emotive Behavior Therapy (REBT) - Ully Arta Silitonga; Nur Annisa Sawitri; Saniya Putri Ayu Febiolantika; Kerin Ari Chaniago; Ratna Sari Dewi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Based on various studies and studies, the LGBT phenomenon in Indonesia, especially in the Pekanbaru area, is still often viewed negatively because it is considered contrary to local social and cultural norms. Several factors that influence the emergence of LGBT sexual orientation include childhood experiences, the influence of the social environment, and conditions within the family. Psychological interventions such as group counseling with the Rational Emotive Behavior Therapy (REBT) approach combined with religious values, such as in Islamic counseling, have proven effective in reducing inner conflict, increasing the ability to manage emotions, and encouraging acceptance and self-confidence of LGBT individuals. This approach also helps replace irrational thought patterns and strengthens emotional resilience, although cultural and social challenges are still major obstacles. On the other hand, the importance of multicultural competence for professionals is also highly emphasized in dealing with issues related to LGBT and their emotional health. Education about sexuality and increasing public understanding of diversity are considered important to reduce stigma and discrimination against the LGBT community. Overall, the results of this study indicate the need for an appropriate psychological approach and educational efforts to create social acceptance and improve the welfare of LGBT individuals.